How big things get done : the surprising factors that determine the fate of every project, from home renovations to space exploration and everything in between - Flyvbjerg, Bent; Gardner, Dan, 1968- (Currency, 2023)
An Oxford economist and expert on mega-projects examines how the lessons learned through both their successes and failures can be applied to decision-making about any size project.